The Vicious Cycle of Internet Addiction: Analyzing Theories and Correlations with Adolescent Well-being - Sharma, Gauri; Srivastava, Kiran (Journal of Neonatal Surgery, 2025)
The essence of digital transformation and its vicious cycle impacting on the well-being of adolescents is evident in the current time. The criticality of internet induced addiction and its consequences can lead to significant accumulation of stress in adolescents. The study here would relate the internet addiction levels while analyzing the existing set of research frameworks that can be associated with it. A mixed method approach is undertaken where secondary sources from current literature and 500 adolescents in the age group of 14 to 18 years from India are taken. The results exhibit the commonly used theoretical frameworks in this domain and find a significant correlation between internet addiction, mental health and general well-being of adolescents. There are implications for the future provided with association of these results with the common theoretical frameworks extracted from literature